Trade Union Strategies and Legacy of the 1960s in Student Mobilization in Turkey: The Case of the Student Youth Union Öğrenci Gençlik Sendikası (Genç-Sen) - Işıl Erdinç (European Journal of Turkish Studies)
The acceleration of neoliberal policies in the mid-1980s led to a rise in social inequality and unemployment during the 2000s in Turkey. Students, influenced by both state repression and the aggravation of economic conditions, became major actors in social movements. The Confederation of Progressive Trade Unions, Devrimci İşçi Sendikaları Konfederasyonu (DİSK), which had been in a period of reconstruction since its reestablishment in 1991, had triggered the foundation of a student union. In 2007, Öğrenci Gençlik Sendikası (Genç-Sen), the first students’ union, in Turkey, was founded. This article, based on observations and interviews conducted in February and March 2011, examines the emergence and the structure of Genç-Sen and the evolution of its discourse and mobilization strategies. I argue that the organization was strongly affected by the legacy of 1960s and 1970s and by the tradition of labour unionism.